Simulation study of a heuristic near-maximum ant-based dynamic routing - Tan, Chin; Fouad, Abbou; Ewe, Tat (ZARKA PRIVATE UNIV, 2008)
A new ant-based routing is proposed for solving dynamic routing and wavelength assignment in mesh WDM network under the wavelength continuity constraint. The ant algorithm favors paths with maximum number of available wavelengths between two nodes, resulting in improved load balancing and less congested shortest path. The simulation results showed that the proposed ant-based routing algorithm is highly reliable in the sense that the number of ants used is predictable to achieve a steady performance in terms of blocking probability.